2020
DOI: 10.9734/cjast/2020/v39i130483
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition and Antioxidant Activity of Balanites aegyptiaca, Securidaca longepedunculata and Acacia gourmaensis Used against Seed-borne Fungi in Burkina Faso

Abstract: Aims: Hydroethanolic extracts of Balanites aegyptiaca, Securidaca longepedunculata and Acacia gourmaensis from Burkina Faso were investigated for their phytochemical composition and their antioxidant activities. Methods: Highperformance thinlayer chromatography (HPTLC) method was used for phytochemical screening. The total phenolic, total flavonoid and anthocyanin contents of extracts CJAST, 39(1): 79-87, 2020; Article no.CJAST.54710 80 were assessed. The antioxidant potentials of the extracts were also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
0
4
1
1
Order By: Relevance
“…These tests include the 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and Trolox Equivalent Antioxidant Capacity (TEAC) assays, among others. Several studies have shown a positive correlation between the measured antioxidant activity and the phenolic content [61,75,76]. However, since the test is dependent on the phenolic content, values of the antioxidant activity are also dependent on the extraction solvent, extraction time, extraction method as well as the other factors cited earlier that affect the phenolic content determined from a given plant sample [61].…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…These tests include the 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and Trolox Equivalent Antioxidant Capacity (TEAC) assays, among others. Several studies have shown a positive correlation between the measured antioxidant activity and the phenolic content [61,75,76]. However, since the test is dependent on the phenolic content, values of the antioxidant activity are also dependent on the extraction solvent, extraction time, extraction method as well as the other factors cited earlier that affect the phenolic content determined from a given plant sample [61].…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…As for the tannins, the plate was sprayed with a 2% FeCl 3 reagent. Evaluation was performed under white light [25].…”
Section: High-performance Thin Layer Chromatography (Hptlc) Screeningmentioning
confidence: 99%
“…Each raw extract was subjected to phytochemical screening. Tannins, flavonoids, alkaloids, saponins, and triterpenes were searched for on the various extracts using standard procedures as described in the literature (Wagner and Bladt., 1996;Békro et al, 2007;Ramde-Tiendrebeogo et al, 2019;Nitiema et al, 2020).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Similarly, other studies have shown the effectiveness of plant extracts on this tick in Benin (Adehan et al, 2016), in Brazil (Silva et al, 2017;Politi et al, 2019) in India ( Kumar et al, 2012) in New Caledonia (Lebouvier et al, 2013). To find new sources of natural acaricides, we were interested in three aromatic plants from Burkina Faso (Ocimum gratissimum, Ocimum americanum, and Laggera oloptera) whose biological activities have been reported in numerous works including their insecticidal properties (Nébié, 2006;Ouédraogo et al, 2016;Tia et al, 2019). The present study, therefore, aimed at assessing the acaricide efficacy of the extracts of these three plants on adults of the tick R. (B.…”
Section: Introductionmentioning
confidence: 99%